Pertumbuhan Stek Batang Buah Naga (Hylocereus costaricensis L.) Berbagai Ukuran Akibat Pemberian Air Kelapa Dengan Cara Yang Berbeda - Didik Setiawan; Syafiuddin Syafiuddin; Jamaludin Jamaludin; Yatmin Yatmin (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
Dragon fruit is one type of plant that is quite popular in Indonesia because of its sweet taste and high selling price. Dragon fruit has various types, including dragon fruit with red flesh, white flesh with yellow skin color and red skin with white flesh. Dragon fruit contains high betacharotene and antioxidants to prevent cancer and ward off free radicals. The fiber content in it can facilitate digestion, prevent colon cancer, and cope with diabetes. The objectives of this study were to determine effect of length stem cuttings on the growth of red dragon fruit cuttings, effect of different methods of giving between immersion and watering coconut water on the growth of dragon fruit cuttings, and interaction lengths cuttings and how to give coconut water to the growth of dragon fruit cuttings. The results showed that red dragon fruit stem lengths of 25 cm and 30 cm give better results than 15 cm and 20 cm. Dragon fruit stem lengths of 25 cm and 30 cm had a significant effect on bud emergence variables, number of shoots, average shoot length per cuttings and number of roots, but the root length variables, root wet weight and root shoot ratio were not significantly different. The method of giving coconut water shows that watering is better than soaking. but on the variable number of shoots per cuttings, the average length of shoots per cuttings, root wet weight and root crown ratio had no significant effect. There is no interaction between rod length and means giving coconut water to the growth of red dragon fruit cuttings on all observed variables.